أثر الصادرات في النمو الاقتصادي لدول مجلس التعاون الخليجي للمدة (1990-2014 ) "دراسة قياسية" - AL-Thalabi, Sahera; AL-Dirawi, Raisan (مجلة العلوم الإدارية و الإقتصادية, 2018)
This study aims to display the role of the export sector and external trade in the performance of the economic growth in gulf cooperation countries and the standard approach used in the study rely on the style of analyzing estimated relationship for each country alone through the time series (1990-2014)and also rely on using the style of analyzing to combine the time series with the sectional data In the conclusion the study refer to the regression parameters are matched with economic theory logic in the individual modal, Except the investment parameters in the Bahrain. and the explanatory variables have a significance statistical in Saudi Arabia. as only the value of export with significance statistical in the rest of the countries, the panel data showed the results in the style of the preference relate to the regression synthesis modal and the result made clear that export coefficient of EXP is statistically and the local investment coefficient IN is non-significant and the high moral for the modal as a whole and for all the forms.